2013
DOI: 10.1093/jac/dkt101
|View full text |Cite
|
Sign up to set email alerts
|

Do statins protect against the development of Clostridium difficile-associated diarrhoea?

Abstract: Prior statin use may provide protection against CDAD. Further studies are warranted to evaluate this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 42 publications
1
26
1
Order By: Relevance
“…Similarly, statin use may constitute a measure of increased healthcare access in our study. The relationship of statin use and CDI remains a subject of interest in the literature 18,19 , although the nature and direction of this relationship is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, statin use may constitute a measure of increased healthcare access in our study. The relationship of statin use and CDI remains a subject of interest in the literature 18,19 , although the nature and direction of this relationship is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial and antifungal agents, bacterial and fungal probiotics, steroids and other immunosuppressants, statins, 18,19 proton pump inhibitors (PPIs), 20 and anti-diabetes medications 21 recorded within the 180-day window prior to the CDI diagnosis were included. Antibacterial agents were classified into low, moderate, and high CDI risk strata (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Existing clinical evidence suggests that statins reduce the incidence of coronary disease (Nissen et al, 2005; Ridker et al, 2005), rheumatoid arthritis (Chodick et al, 2010), Alzheimer's disease (Di Paolo and Kim, 2011), chronic obstructive pulmonary disease (Cao et al, 2015), and gastric cancer (Lin et al, 2016). Most importantly, statins have been reported to protect against bacterial infectious diseases (Jerwood and Cohen, 2008; Nseir et al, 2013; Skerry et al, 2014; Lin et al, 2016). The combination treatments including triple therapies and statins facilitated H. pylori clearance and attenuated ulcer development (Tariq et al, 2007; Yamato et al, 2007; Nseir et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Statins are inhibitors for 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG-CoA) reductase and have been found to play a protective role in several bacteria-associated diseases (Jerwood and Cohen, 2008; Nseir et al, 2013; Skerry et al, 2014). Previous studies have reported that combination treatments, including triple therapies (consisting of a proton-pump inhibitor, amoxicillin, and clarithromycin) prescribed along with statins, accelerate H. pylori clearance and ameliorate ulcer development (Tariq et al, 2007; Yamato et al, 2007; Nseir et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a matched case-control study, there was a lower incidence of CDI in the statin group compared with the non-statin group (adjusted OR: 0.78; 95% CI: 0.76-0.84) [155]. A retrospective case-control study of patients with CDI demonstrated that there was a lower incidence of CDI in the statin group (64/ 197 32.5%) compared with the non-statin group (87/169 51.5%) [156]. A retrospective study found lower recurrence in CDI rates for patients in the statin group compared with the non-statin group [157].…”
Section: Statinsmentioning
confidence: 95%